Utilizing YouTube for The Local Film Culture Expansion - Dyna Herlina Suwarto; Firly Annisa; Febriansyah Kulau (Universitas Muhammadiyah Yogyakarta, 2023)
This article explore the role of YouTube in developing local film culture. The Covid-19 pandemic has disrupted various local short film festivals and screenings. Local filmmakers are trying to find alternative channels to show their short films via YouTube. Using the media industries studies perspective, this research offers two cases, Tilik and Loz Jogjakartoz, to study the role of YouTube for local film the promotion and distribution. Based on in-depth interviews, Ravacana Films and Kebon Ijo Studio implement specific strategies such as film upload timing, social media promotion and audience attention management so that their films trend on YouTube. This research reveals that YouTube can play an important role in connecting local filmmakers with audiences and the national film industry.